Costume and design for devised and physical theatre - Bicat, Tina (Ramsbury, Marlborough, Wiltshire Crowood Press, 2012)
A practical guide to costume for devised and physical theatre, this title outlines the differences between designing for scripted and for devised work.
The world of devised and physical theatre. -- Invention in the rehearsal room. -- Communication and meetings. -- Discovering the style and creating the designs. -- Design in rehearsal. -- Shopping and sourcing. -- Cutting for movement. -- Fittings. -- Costume for extreme physical movement. -- Accessories, extras and costume objects. -- The technical and dress rehearsal and the show.
Includes index.
Keywords: Costume design; Dance costume